"Deidamia Achilli" – średniowieczny dialog z "Heroidami" Owidiusza w przekładzie na język polski - Miazek-Męczyńska, Monika (Collectanea Philologica, 2024)
The article presents the first translation into Polish of an anonymous medieval poem entitled Deidamia Achilli. It belongs to the rich tradition of continuation and imitation of Ovid’s Heroides. The dependencies of the medieval text on Ovid’s elegies (especially Her. III) are shown, as well as its connections with Statius’ Achilleis.